Understanding the use of over-the-counter pain treatments in adolescents with chronic pain. Issue 1 (1st January 2017) - Stinson, Jennifer; Harris, Lauren; Garofalo, Elizabeth; Lalloo, Chitra; Isaac, Lisa; Brown, Stephen; Tyrrell, Jennifer; Ruskin, Danielle; Campbell, Fiona
ABSTRACT: Background : The prevalence of chronic pain in children and adolescents is well established. What is not well understood is how over-the-counter (OTC) oral and topical pain treatments are being used by adolescents with chronic pain, their decision making around use of these products, and how they communicate with their health care providers about their use. Aims : The aim of this study was to explore the use, decision-making process, and communication about the use of OTC pain medications with health care professionals among adolescents living with chronic pain and their primary caregiver. Methods : A qualitative descriptive design with semistructured, audiotaped individual interviews was undertaken with adolescents with chronic pain ( n = 15, aged 12–18 years, mean age = 16, SD = 1.79) and their caregivers ( n = 16). A convenience sample of patient–caregiver dyads was recruited from a tertiary care pediatric chronic pain clinic in Ontario. Results : Interview questions focused on four topics: (1) experience with chronic pain and medication; (2) perceptions of medications and concerns with long-term consumption; (3) decision making for use of OTC medications guided mainly by a trusted source or health care professional; and (4) topical OTC medications perceived as harmless. Content analysis within these four topics uncovered two to four subthemes, which are described in detail. Conclusions : An improved understanding of the prevalence of use, decision-making process around use, and how patients and their families communicate about the use of OTC pain medications with health care providers can help clinicians better personalize treatments and help adolescents with chronic pain to make sound self-care decisions.